Peran Pelayanan Publik 112 Dalam Meningkatkan Responsivitas Penanganan Darurat di Kota Mojokerto - Theofila Chevara Aira Nazaputri; Diana Hertati (Public Service and Governance Journal, 2025)
The 112 emergency service is a system designed to provide a quick response to life-threatening emergency situations, such as traffic accidents, fires and crimes. This research aims to evaluate the effectiveness of the implementation of the 112 service in Mojokerto City in coordination between agencies such as the Civil Service Police Unit, Mojokerto Police, Health Service, and other related agencies. Using a qualitative descriptive method combining several data collection methods, this research analyzes the responsiveness of services that operate 24 hours non-stop and toll-free. The research results show the important role of public services 112 in increasing the responsiveness of emergency handling. The research concludes that the implementation of this service has contributed significantly to increasing the responsiveness of emergency management in the city of Mojokerto, as well as identifying the strengths and challenges in implementing the 112 emergency service in the city of Mojokerto.